Experimental study on stability and heat transfer characteristics of separated heat pipe with a compressible volume condenser - Jinle Zhao; Qincheng Bi; Teng Wang; Tao Zhang; Fan Feng (Case Studies in Thermal Engineering)
A novel Separated Heat Pipe (SHP) system incorporating two magnetic spheres (SHPMS) was proposed for power generation (US Patent 11365653B2, 2022) using low-grade thermal energy, or offering both reliable emergency power and efficient heat transfer for spent fuel pools. This paper reports the experimental investigation on flow and heat transfer characteristics of the SHP, providing a foundation for the R&D of SHPMS. The SHP system features a unique shell-and-tube condenser structure, where the tube side serves as the cooling coil, while the shell side functions as the condenser chamber, with the dual roles of liquid storage and surge tank. The study researched the stability and heat transfer performance of the SHP under various parameters, including filling ratios ranging from 17 % to 98 %, cooling temperatures between 14 °C and 22 °C, and system pressures from 630 to 830 kPa. Analysis of instantaneous temperature, pressure, and flow patterns reveals the absence of high-frequency oscillations or alternating flow patterns, indicating that the condenser's condensing chamber may eliminate the instability in the SHP. Comparative analysis of the heat transfer coefficient and thermal resistance indicates that higher filling ratios and system pressures impair heat transfer performance, with optimal results at lower filling ratios (17 %–55 %) and pressure (630 kPa), where the higher heat transfer coefficient and lower thermal resistance were observed. Cooling temperatures showed little impact on heat transfer, allowing it to be chosen based on safety and energy efficiency needs. This study provides a new perspective on SHP systems with compressible volume condenser, offering a potential solution to address the instability challenges of SHP and the selection of operation parameters.